DIALECTICS OF INTRA-PARTY OPPOSITION IN NIGERIA’S FOURTH REPUBLIC: INSIGHTS FROM THE RULING PEOPLE’S DEMOCRATIC PARTY (PDP) - Okoli, Al Chukwuma; Ali, Ali Haruna (European Scientific Journal, ESJ, 2014)
This paper examines the essence and contradictions of intra-party opposition in Nigeria’s Fourth Republic with a view to underscoring its implications for democracy. This is against the backdrop of the rising incidence of wrangling and fractionalization particularly within the ruling People’s Democratic Party (PDP), leading first to the emergence of a splinter party and then massive defections to the opposition party. By way of qualitative exploration and interrogation of secondary sources, the paper observes that the phenomenon of intra-party opposition is precipitated by the norm-less character of politics and partisan relations, which has been exacerbated by the ideological bankruptcy of political parties in Nigeria. From the standpoint of the PDP crisis in Anambra State (1999–2003), as well as the national PDP saga (2013/2014), the paper posits that intra-party opposition depicts one of the structural contradictions of party politics in Nigeria, which portends negatively for democratic consolidation. The paper makes a case for ideology-based partisanship as a panacea to the problem.